THE FEATURES OF ANTIHYPERTENSIVE THERAPY IN PATIENTS WITH METABOLIC SYNDROME - L. V. Kremneva; O. V. Abaturova; S. V. Shalaev (Столичная издательская компания, 2015)
Arterial hypertension (HT) in patients with metabolic syndrome has features (early damage of target organ, a predisposition to thrombosis, refractory to standard antihypertensive therapy, high cardiovascular risk). The aim of HT treatment in patients with metabolic syndrome includes not only the achievement of target blood pressure, but also a reduction of target organ damage, correction of modifiable risk factors and associated clinical conditions. Results of multicenter studies on assessment of clinical efficacy of groups of antihypertensive drugs, their effects on metabolic parameters, the ability to prevent the development of cardiovascular events, diabetes mellitus, and renal dysfunction are presented.